Pengaruh Jenis Poliol terhadap Pembentukan Poliuretan dari Monomer PEG400 dan MDI - Eli Rohaeti; N. M. Surdia; Cynthia L. Radiman; E. Ratnaningsih (Journal of Mathematical and Fundamental Sciences, 2003)
The properties of polyurethane depend largely on building blocks, especially the kind of polyol. Not only pure synthetic compounds but also various natural substances such as saccharides (glucose, fructose, maltose, sucrose) and amylose can be used as possible resources of polyol in polyurethane synthesis. Those natural substances are natural polymeric materials having appropriate reactivity thank to its functional groups such as hydroxyl groups. Natural polymers having more than two hydroxyl groups per molecule can be used as polyols for polyurethane synthesis. In this study, the effect of addition of saccharide (glucose, maltose) and amylose in the synthesis polyethylene glycol 400 (PEG400) and methylene-4,4'-diphenyldiisocyanate (MDI) based polyurethane was studied by measuring the hydrogen bonding index (HBI) and the thermal properties. Characterization of functional groups in resultant polyurethane was analyzed by FTIR spectrophotometry, the thermal properties were conducted with Differential Thermal Analysis (DTA), Differential Scanning Calorimetry (DSC), and Thermal Gravimetric Analysis (TGA). The addition of saccharide (glucose, maltose) and amylose on the synthesis polyurethane from polyethylene glycol 400 (PEG400) and methylene-4,4'-diphenyldiisocyanate (MDI) can increase the hydrogen bonding index and the glass transition temperature of polyurethane. In all case the increase of glucose unit in polyol can increase the hydrogen bonding index, the glass transition temperature, and the thermal stability of polyurethane.